2020
DOI: 10.5032/jae.2020.03144
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Relationship Between Goal Orientation and Individual Characteristics Amongst Agricultural Leadership Development Program Participants

Abstract: The importance of knowing and employing strategies to effectively motivate learners is well established. This is also true for leadership educators that have a mandate to build leadership capacity amongst learners in various environments. However, despite the importance of learner motivation in learning environments, there has been a lack of empirical studies to determine if there may be dispositional trends related to motivational tendencies based on demographic categories, specifically within adult agricultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 45 publications
(108 reference statements)
0
10
0
Order By: Relevance
“…A reasonable ground for this isolation is that many recent studies have been published investigating the relationships between the construct of goal orientation and self-efficacy (Curelaru, 2020); goal orientation and emotional intelligence and burnout (Supervía et al, 2020a); goal orientation and engagement and self-concept (Supervía et al, 2020b); goal orientation and emotional intelligence and burnout (Supervía and Bordás, 2020); goal orientation and positive coping strategy and motivational beliefs (Subaşı, 2020); goal orientation and academic achievement (Giota and Bergh, 2020;Moghimi, 2020); goal orientation and individual characteristics (Lamm et. al., 2020); and goal orientation and motivation (Hidajat et al, 2020).…”
Section: The Importance Of Academic Goal Orientationmentioning
confidence: 99%
“…A reasonable ground for this isolation is that many recent studies have been published investigating the relationships between the construct of goal orientation and self-efficacy (Curelaru, 2020); goal orientation and emotional intelligence and burnout (Supervía et al, 2020a); goal orientation and engagement and self-concept (Supervía et al, 2020b); goal orientation and emotional intelligence and burnout (Supervía and Bordás, 2020); goal orientation and positive coping strategy and motivational beliefs (Subaşı, 2020); goal orientation and academic achievement (Giota and Bergh, 2020;Moghimi, 2020); goal orientation and individual characteristics (Lamm et. al., 2020); and goal orientation and motivation (Hidajat et al, 2020).…”
Section: The Importance Of Academic Goal Orientationmentioning
confidence: 99%
“…Currently, only one study (Lamm et al, 2020a) linking goal orientation and agricultural-related leadership development programming exists. Lamm et al (2020a) found that adult learners' goal orientation disposition may be correlated with demographics such as age and status in the organization.…”
Section: Related Literaturementioning
confidence: 99%
“…Currently, only one study (Lamm et al, 2020a) linking goal orientation and agricultural-related leadership development programming exists. Lamm et al (2020a) found that adult learners' goal orientation disposition may be correlated with demographics such as age and status in the organization. A statistically significant correlation was found between age and PGO-P, implying that older employees may not feel the pressure to prove themselves as much as they once did thanks to their years of experience.…”
Section: Related Literaturementioning
confidence: 99%
See 2 more Smart Citations